Effect of increased feeding of dietary α‐linolenic acid by grazing on formation of the cis9, trans11–18:2 isoform of conjugated linoleic acid in bovine milk. (23rd November 2016) - Yamaguchi, Mio; Naito, Taki; Nagao, Yoshikazu; Kabuyama, Yukihito; Hashimoto, Kei; Azuma, Norihiro; Maeda, Isamu
Abstract: Feeding systems such as grazing affect the fatty acid profile of bovine milk fat. In addition, milk fat is formed as the product of fatty acid metabolism in cow bodies before being secreted into milk. However, how grazing influences milk fatty acid profile through the metabolism has not been completely characterized. When fatty acid concentrations in Holstein milk were compared between grazing and non‐grazing periods, α‐linolenic acid was significantly higher in the grazing period than in the non‐grazing period. This could be explained with an increase in α‐linolenic acid feeding with grazing. α‐linolenic acid had a linear positive correlation with conjugated linoleic acid (9 c, 11 t ‐18:2) (CLA) and vaccenic acid (VA) during the grazing period, whereas CLA had higher correlation with linoleic acid rather than with α‐linolenic acid during the non‐grazing period. These data indicate that the high content of dietary α‐linolenic acid affects CLA and VA formation in milk of grazing periods via α‐linolenic acid metabolism into VA.